Organizational Communication Dynamics within the Public Sector in the Implementation of Indonesian Bureaucratic Reform Policies - Ahmad Saudi; Andi Kardian Riva’i; A’ang Chaarnaillan (Journal of Creative Power and Ambition (JCPA), 2026)
The successful implementation of bureaucratic reform in Indonesia is heavily determined by the effectiveness of public sector organizational communication. This study aims to analyze the dynamics of organizational communication, including message flow patterns and sociological barriers, in influencing the effectiveness of policy transmission from the central level to technical implementers. This qualitative research employs a literature review method through the collection, condensation, and synthesis of reputable scientific literature. The findings reveal that a rigid, top down communication pattern with an instructional nuance tends to trigger message distortion, misaligned perceptions, and passive resistance among frontline civil servants. Furthermore, policy implementation faces complex constraints, including hierarchical cultural barriers (paternalistic culture), structural informational barriers (sectoral ego), and technical-semantic barriers (divergent interpretations of key performance indicators and limited digital literacy). Reconstructing communication into a more dialogic, transparent, and inclusive approach is proven to enhance active participation and the affective commitment of State Civil Apparatus. Additionally, accelerating digital communication transformation through the Electronic Based Government System serves as a strategic medium to streamline bureaucratic chains, eliminate sectoral silos, and substantively support the consolidation of the ASN core values "BerAKHLAK" toward achieving accountable and competitive governance.